Prinsip-Prinsip Ekonomi Islam Dalam Al-Qur`An Menurut Tafsir Ibnu Katsir - Fakrurradhi Fakrurradhi (Al Mashaadir : Jurnal Ilmu Syariah, 2021)
The presence of the Islamic economy raises new hope for many people, especially for Muslims. Where what is offered in Islamic economics is believed to be an alternative solution concept of the economic system of capitalism and socialism as the main stream of a concept of a world economic system. In this case, the author examines the principles of Islamic economics in the Qur'an according to Ibn Kathir. The purpose of this research is to find out the principles of Islamic economics in the Qur'an according to Ibn Kathir. In this study, the author uses qualitative research methods that are analytical in nature, and with a document analysis approach (content analysis) or can be said to be library research. The results of this study are the principles of Islamic economics contained in the Qur'an according to Ibn Kasir's interpretation, including the Halal Principle (An-Nisa [4]: 29), the Principle of Equity (Al-Hasyr [59]). ]: 7), the Principle of Equitable Prosperity (Al-Maidah [5]: 8), and the Principle of Not Mutual Mendhalim (Al-Baqarah [2]: 279). It is these principles that are finally achieved that will create economic prosperity for a society that is equitable and just and does not oppress each other. So that Muslims in particular are free from the capitalist economic system.